Dose- and sex-related carcinogenesis by N-bis(2-hydroxypropyl)nitrosamine in Wistar rats - Moreira, ELT; de Camargo, JLV; Rodrigues, MAM; Barbisan, L. F.; Salvadori, DMD (Business Center Academic Societies Japan, 2000)
An initiation-promotion medium-term bioassay for detection of chemical carcinogens, developed in the male F344 rat, uses 0.1% N-bis(2-hydroxypropyl)nitrosamine (DHPN) among five genotoxic chemicals for the initiation of carcinogenesis in multiple organs. To establish this bioassay in the Wistar strain, the effects of two dose levels of DHPN were evaluated on the main DHPN rat target organs: lung, thyroid gland, kidneys and liver. Four groups of male and female animals were studied: Control--untreated group; Multi-organ initiated group (also referred to as DMBDD, based on the initials of the five initiators)-treated sequentially with N-diethylnitrosamine (DEN, i.p.), N-methyl-N-nitrosourea (MNU, i.p.), N-butyl-N-(4-hydroxy butyl)nitrosamine (BBN, drinking water), N, N'-dimethylhydrazine (DMH, s.c.) and DHPN (drinking water) for 4 weeks; a third group treated with 0.1% DHPN in drinking water for 2 weeks and the last group treated with 0.2% DHPN in drinking water for 4 weeks. The animals were sacrificed after 30 weeks. DHPN at 0.2% induced preneoplasia in the liver and kidneys of rats of both sexes, the number and area of the putative preneoplastic liver glutathione S-transferase-positive hepatocyte foci being significantly increased in these animals. It also induced benign and malignant tumors in female and in male rats. However, there was no relationship between the increased incidence of preneoplastic lesions and tumor development in the 0.2% DHPN-exposed groups of both sexes. DHPN at 0.1% induced only a few preneoplastic lesions in the liver and kidney and no tumors in both male and female rats. A clear dose and sex-related carcinogenic activity of DHPN was registered, although Wistar rats of both sexes showed a relative resistance to the carcinogenic activity of this compound.
Keywords: N-bis(2-hydroxypropyl)nitrosamine (DHPN); Wistar rat; multi-organ carcinogenesis; preneoplasia and neoplasia; chemical carcinogens